[News Script: Fischer appeal] - WBAP-TV (Television station : Fort Worth; Tex.) (1972)
Photocopy of a script from the WBAP-TV/NBC station in Fort Worth, Texas, relating a news story about Bobby Fischer not winning his protest against losing.